New Straits Times, 25 September 2008 - Adrian Lasimbang (The New Straits Times Press (M) Bhd, 2008)
With reference to your report "20,000ha gazetted for Orang Asli reserve" (New Sunday Times, Sept 21) we wish to respond to some of the comments made by the Department of Orang Aslu Affairs, specifically the following: